2021
DOI: 10.3390/ani11072079
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of PI3K/Akt/PTEN Pathway in Canine Mammary Tumor

Abstract: The PI3K/Akt/PTEN axis is one of the most important signaling pathways in tumorigenesis. Recently, mutation of PIK3CA has been highlighted due to the similarities of mutational hotspots in both dogs and humans. PIK3CA H1047R (c.3140A > G) has been discovered as the most common mutational hot spot in canine mammary tumor in recent studies, while the feature of PIK3CA-mutated canine mammary tumor is obscure. Methods: A total of 83 mammary samples classified as normal (n = 13), adenoma (n = 25), low-grade carc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…The role of PTEN , one of the main tumor suppressor genes, in down-regulation or mutation/deletion in breast cancers has been shown in other studies [ 42 ]. Herein we report its non-continuous expression; other studies have shown that copy number aberrations of PTEN are associated with negative evolution of CMCs and HBC [ 42 , 43 ]. In the study by Asproni et al [ 44 ], the authors reported that reduction of PTEN immunohistochemical expression can lead to the interruption of the inhibition of the PI3K/AKT pathway, resulting in glycolysis activation for ATP production compared to mitochondrial respiration; therefore PTEN immunohistochemical expression is correlated with less aggressive tumors, no lymphatic invasion, and enhanced survival rates.…”
Section: Discussionmentioning
confidence: 98%
“…The role of PTEN , one of the main tumor suppressor genes, in down-regulation or mutation/deletion in breast cancers has been shown in other studies [ 42 ]. Herein we report its non-continuous expression; other studies have shown that copy number aberrations of PTEN are associated with negative evolution of CMCs and HBC [ 42 , 43 ]. In the study by Asproni et al [ 44 ], the authors reported that reduction of PTEN immunohistochemical expression can lead to the interruption of the inhibition of the PI3K/AKT pathway, resulting in glycolysis activation for ATP production compared to mitochondrial respiration; therefore PTEN immunohistochemical expression is correlated with less aggressive tumors, no lymphatic invasion, and enhanced survival rates.…”
Section: Discussionmentioning
confidence: 98%
“…181 Similar pathway mutations have also been identified in canine mammary gland tumors (cMGTs), including recurrent somatic PIK3CA variants and PTEN deletions with loss of heterozygosity associated with poor prognosis. 8,22,131,132 There are also similarities in gene expression signatures, characterized by PI3K-AKT, PTEN, and MAPK pathway enrichment. 264 PI3K pathway alterations are reported in 50% of cMGT with the PIK3CA H1047R mutation affecting 26% of tumors examined.…”
Section: Mammary Carcinomamentioning
confidence: 99%
“…5 However, continued research is required to elucidate the indirect correlation between mutation status and PI3K-AKT-mTOR pathway dysregulation in cMGT. 118,131 In an immunohistochemical study of cMGTs, greater PI3K immunoreactivity was significantly associated with regional lymph node infiltration, distant metastasis, ERBB2+ tumors, and the lowest survival rate. 208 The study found a positive correlation between PI3K immunoreactivity and triple-negative tumors compared with those with hormone receptor expression, as well as greater PI3K immunoreactivity in luminal B phenotype versus luminal A.…”
Section: Mammary Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…14 Thus, HHT may inhibit tumour growth in CMC. Kim et al found using Sanger sequencing that AKT and p-AKT are abnormally expressed in CMC, 15 which may be associated with cancer occurrence and development. Therefore, searching for small-molecule drugs that inhibit the AKT pathway has become a focus of attention.…”
mentioning
confidence: 99%